Anthocyanin enriched guava nectar: An alternative source of antioxidant biofortification - Singh, Ajit Kumar; Sagar, Vidya Ram; Singh, Sanjay Kumar; Sethi, Shruti; Shankar, Kripa (Indian Horticulture, 2023)
The ratio of 50:50 of guava and coloured grape blends is most acceptable for the preparation of anthocyanin rich guava nectar with maximum retention of anthocyanins, flavour and other nutrient retention. Coloured grape juice has anthocyanins in abundance and relatively inexpensive source for natural colouring of food and beverage products. However, during storage, coloured bottles performed better over transparent bottles with respect to sensory and nutritional qualities of the nectar irrespective of the storage conditions. Therefore, blending of two or more fruit juices and their beverages are thought to be a convenient alternative for their utilization in order to have novel and appealing value-added fruit drinks, which are of high quality in respect of both sensory and nutraceautical properties and can be a new entrepreneurial venture for youths.